Sureq, Lontaraq, Toloq: Manuskrip dan ragam sastera Bugis - Sirtjo Koolhof (Universiti Kebangsaan Malaysia, 2007)
Since the 1970s, Bugis written literature has been usually classified into two categories, sureq (literature, belles lettres) and lontaraq (prose texts with a more practical orientation, often of a historiographic nature). Although most scholars accept this classification, the Bugis manuscript tradition does not support this dichotomy. In this article, the use of these terms, as well as the term toloq (usually translated as ‘heroic poem’) is analyzed based on the manuscript tradition. This analysis finds no support for the use of these terms for literary genres, but shows instead that they refer to manuscripts as physical objects and that their use to classify genres of literature is artificial